The life and times of the honeybee - Micucci, Charles (Boston : Houghton Mifflin, 1995)
Depicts the life cycle and habits of the honeybee, describing in detail the organization of the hive and the making of honey.
Wilson's Children.
Elem. School Library Collection.
School Library Journal starred.
3.0
K-3
Keywords: Honeybee -- Juvenile literature; Bee culture -- Juvenile literature; Honey -- Juvenile literature; Honeybee; Bee culture; Honey; Honeybees; Honey; Bees; Honeybee; Bees; Honey